ECONOMIC SHIFT AND INEQUALITY BETWEEN PROVINCES IN SULAWESI ISLAND, REPUBLIC OF INDONESIA - I Kadek Satria Arsana; Fahrudin Zain Olilingo (LP2M Universitas Bina Mandiri Gorontalo, 2021)
AbstraCT The study aimed to investigate shifts in economic growth as well as inequality of development between provinces in Sulawesi Island by Klassen typology analysis and Williamson Index. The result revealed that during the last five years up to the research timeline (2014-2018), two of six provinces in the island experienced economic decline. The inequality rate in Sulawesi Island is relatively low, as reflected by the average Williamson Index value that is approaching zero or 0.0796. The Williamson Index value in 2014 was 0.142, higher than the value in 2018, scoring 0.036. The number suggests significant decline in inequality rate. Therefore, equal distribution of economic growth is essential by developing sectors with potential contribution in boosting the region’s GRDP. Moreover, the study also views the importance of taking into consideration the three causes of economic inequality, i.e., the region’s demographic character, human resources, and foreign investment rate.